Mean HbA1c, HbA1c variability, and mortality in people with diabetes aged 70 years and older: a retrospective cohort study. Issue 6 (June 2018) - Forbes, Angus; Murrells, Trevor; Mulnier, Henrietta; Sinclair, Alan J
Summary: Background: Glycaemic targets for older people have been revised in recent years because of concern that more stringent targets are associated with increased mortality. We aimed to investigate the association between glycaemic control (mean HbA1c ) and variability (variability of HbA1c over time) and mortality in older people with diabetes. Methods: We did a 5-year retrospective cohort study using The Health Improvement Network database, which includes data from 587 UK primary care practices. We included patients of either sex who were aged 70 years and older with type 1 or type 2 diabetes. The primary outcome was time to all-cause mortality. Our primary exposure variables were mean HbA1c and variability of HbA1c over time. The observation included a 4-year run-in period (from 2003) as a baseline, with a 5-year follow-up (from 2007 to 2012). We assessed mean HbA1c in three models: a baseline mean HbA1c for 2003–06 (model 1), the mean across the whole follow-up period (model 2), and a time-varying yearly updated mean (model 3). A variability score (from 0 [low] to 100 [high]) was calculated on the basis of number of changes in HbA1c of 0·5% (5·5 mmol/mol) or more from 2003 to 2012 or to the point of mortality, based on changes in the annual mean as per each model with a minimum of six readings. Findings: The cohort consisted of 54 803 people, of whom 17 680 (8614 [30·7%] of 28 017 women and 9066 [33·8%] of 26 786 men) died during the observation period. The overall mortality rate was 77 per 1000 person-years (73 per 1000 person-years for women and 80 per 1000 person-years for men). The data showed a J-shaped distribution for mortality risk in both sexes, with significant increases with HbA1c values greater than 8% (64 mmol/mol) and less than 6% (42 mmol/mol), although excess mortality risk was non-significant in model 1 for men at HbA1c values of 8% (64 mmol/mol) to less than 8·5% (<69 mmol/mol) and in models 1 and 3 for both sexes assessed individually at HbA1c values less than 6% (42 mmol/mol). Mortality increased substantially with increasing HbA1c variability in all models (overall and for both sexes). For the model 2 HbA1c measure, the adjusted hazard ratios comparing patients with a glycaemic variability score of more than 80 to 100 with those with a score of 0 to 20 were 2·47 (95% CI 2·08–2·93) for women and 2·21 (1·87–2·61) for men. Fitting the mean HbA1c models with the glycaemic variability score altered the risk distribution; this observation was most marked in the model 2 analysis, in which a significant increased risk was only apparent with HbA1c values greater than 9·5% (80 mmol/mol) in women and 9% (75 mmol/mol) in men. Interpretation: Both low and high levels of glycaemic control were associated with an increased mortality risk, and the level of variability also seems to be an important factor, suggesting that a stable glycaemic level in the middle range is associated with lower risk. Glycaemic variability, as assessed by variability over time in HbA1c, might be an important factor in understanding mortality risk in older people with diabetes. Funding: King's College London and Diabetes Frail.